Koye kacang powder forming machine - Shamsudin, Rosnah; Zainuddin, Muhammad Fakhri; Mohd Adzahan, Noranizan; Ramli, Noor Azwani (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
A Koye Kacang Powder Forming Machine was designed to compact powder form mixture to certain shape with designed mold in order to make traditional cookie such as kuih putu kacang and koye kacang.The machine is simple and easy to operate. It can be a efficient solution to replace traditional manual method which is time consuming and labor intensive. The footprint of machine is 1570mm x 668mm and the height is 1800mm. The machine consists of pneumatic, compression cylinder, upper mold, center plate with mold and lower collecting tray. There are three main mechanisms which are powder mixture filling, compression and cookies collection. The powder mixture with ingredient of grinded green beans, grinded sugar and water was loaded manually into the automatic filling module with tray. The mixture is then falling into center mold. The sequence follows by mixture compaction by upper mold with concave shape. The step of mixture filling and compaction are repeated for second time to ensure perfection of cookie in term of shape. The process ends when all the cookies are collected after the collecting tray moving down and being taken out manually. The new tray is loaded again and whole process is repeated. The invention can improve the quality of kuih koye kacang in term of size, shape and texture. This technology eliminates human handling error, improves hygiene level, increases production efficiency as well as reducing labor cost.